Nonlinear reply of radon and deterministic chaos - Kamışlıoğlu, Miraç; Külahcı, Fatih; Özkaynak, Fatih (cmsim.org, 2013)
Many studies have been achieved in applied sciences on the earthquake prediction by researchers. The chaotic non-linear structural behaviour of earthquakes is well known. In order to understand the formation of seismic activity it is extremely important to record the continuous measurements of the soil radon gas (222Rn). In this study, 2976 data of 222Rn are used and the chaotic time series analysis is applied to 222Rn data from the soil. Chaos theory provides a structured explanation for irregular behavior of 222Rn and gas anomalies in systems that are not stochastic. Lyapunov exponents and correlation dimension method are used to show the existence of chaos time series. Chaotic behavior of 222Rn has been showed. Application of methodologies is achieved for Gölcük Region, İzmit, Turkey, where it is seismically very active. © 2019 Institute of Mathematical Statistic. All rights reserved.
6th International Conference on Chaotic Modeling and Simulation, CHAOS 2013 -- 11 June 2013 through 14 June 2013 -- Istanbul -- 151085
Keywords: Chaos analysis; Chaotic modeling; Chaotic time series analysis; Radon measurement